2013
DOI: 10.3390/e16010405
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Properties and Deformation Behaviors of Multi-Component (AlCrTaTiZr)NxSiy High-Entropy Coatings

Abstract: Abstract:In this study multi-component (AlCrTaTiZr)N x Si y high-entropy coatings were developed by co-sputtering of AlCrTaTiZr alloy and Si in an Ar/N 2 mixed atmosphere with the application of different substrate biases and Si-target powers. Their nanomechanical properties and deformation behaviors were characterized by nanoindentation tests. Because of the effect of high mixing entropies, all the deposited multi-component (AlCrTaTiZr)N x Si y high-entropy coatings exhibited a simple face-centered cubic soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…28 Several studies on multi-component nitride coatings have studied the variation of Si content in the materials. 56,[61][62][63] A secondary amorphous phase is indeed formed at high enough Si contents; see, e.g., Fig. 8 showing HRTEM images from Lin et al 63 However, it seems that the attained nanocomposite is more diffuse than the well-known ternary super-hard materials (e.g., nc-TiN/a-Si 3 N 4 ) and thus does not lead to the same hardening.…”
Section: Journal Of Applied Physicsmentioning
confidence: 92%
See 2 more Smart Citations
“…28 Several studies on multi-component nitride coatings have studied the variation of Si content in the materials. 56,[61][62][63] A secondary amorphous phase is indeed formed at high enough Si contents; see, e.g., Fig. 8 showing HRTEM images from Lin et al 63 However, it seems that the attained nanocomposite is more diffuse than the well-known ternary super-hard materials (e.g., nc-TiN/a-Si 3 N 4 ) and thus does not lead to the same hardening.…”
Section: Journal Of Applied Physicsmentioning
confidence: 92%
“…56,[61][62][63] A secondary amorphous phase is indeed formed at high enough Si contents; see, e.g., Fig. 8 showing HRTEM images from Lin et al 63 However, it seems that the attained nanocomposite is more diffuse than the well-known ternary super-hard materials (e.g., nc-TiN/a-Si 3 N 4 ) and thus does not lead to the same hardening. 62,63 It may be that such a distinct nanocomposite structure will prove to be elusive in multicomponent nitrides, as increased solubility in the metal nitride phase may prevent the formation of a distinct tissue phase.…”
Section: Journal Of Applied Physicsmentioning
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, based on the HRTEM observations, Cheng et al [174] and Lin [129] et al reported the formation of the nanocomposite structure in the (AlCr-TaTiZr)SiN coatings produced by the reactive RFmagnetron sputtering, and the hardness values of 34.5 and 30.2 GPa were obtained, respectively. The HRTEM images of the (AlCrTaTiZr)Si 0.15 N 1.07 coating were displayed in Figure 19 [129]. However, it can be seen that the nanocrystalline phase is elongated, rather than equiaxed, which is a typical feature of the nanocomposite films, as shown in Figure 14.…”
Section: Si-containing Hea Nitride Films and Nanocomposite Structuresmentioning
confidence: 99%
“…They attributed the extended solubility of Si to the high entropy effect. Lin et al [39] reported the formation of the nanocomposite structure in the (AlCrTaTiZr)SiN coatings produced by the reactive RF-magnetron sputtering, and found that the nanocrystalline phase is elongated, rather than equiaxed, which is a typical feature of the nanocomposite films. Moreover, the lattice can be observed within the denoted "amorphous regions", suggesting the probable crystallized feature in these regions.…”
Section: The Formation Of the Nanocomposite Structuresmentioning
confidence: 99%